2016
DOI: 10.1039/c5dt04747a
|View full text |Cite
|
Sign up to set email alerts
|

The unusual metal ion binding ability of histidyl tags and their mutated derivatives

Abstract: Polyhistidine-tags are often used for the affinity purification of polyhistidine-tagged recombinant proteins. These sequences are also found in nature and are often highly conserved across different species. However, their exact role in the biological systems is not clear. The purpose of this work is to shed light on the behavior of poly-His sequences in their interactions with metal ions. This work illustrates the first study of novel poly-(His-Ala) peptides that bind Cu(ii) applying both experimental techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 62 publications
1
25
0
Order By: Relevance
“…5 , 6 ). We compared our MB3 and MB6 ligands with two other His-rich peptides, a typical (His) 6 tag (Ac-HHHHHH-NH 2 ) and a snake venom peptide fragment with nine consecutive histidines (Ac-EDDHHHHHHHHH-NH 2 ) [ 1 , 2 , 41 , 42 ]. In the case of zinc complexes, the outcome of these comparisons is easier to explain—both our 18-His and 22-His fragments (MB3 and MB6, respectively) bind Zn 2+ with higher affinity than the His 6 -tag and the 9-His fragment (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…5 , 6 ). We compared our MB3 and MB6 ligands with two other His-rich peptides, a typical (His) 6 tag (Ac-HHHHHH-NH 2 ) and a snake venom peptide fragment with nine consecutive histidines (Ac-EDDHHHHHHHHH-NH 2 ) [ 1 , 2 , 41 , 42 ]. In the case of zinc complexes, the outcome of these comparisons is easier to explain—both our 18-His and 22-His fragments (MB3 and MB6, respectively) bind Zn 2+ with higher affinity than the His 6 -tag and the 9-His fragment (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…These results confirm the previous observation that with the increase of the number of histidines, the coordination becomes more effective. [27][28][29][30] It is important to emphasize that L3 contains both the other two peptides. No direct evidence on the preferred metal binding site of L3 is available, although the higher affinity of L1 with respect to L2 suggests that the distribution of mono-nuclear species where the metal ion is bound to L3 is unbalanced in favour of the Nterminal binding site.…”
Section: A Comparison About Metal Binding Abilitiesmentioning
confidence: 99%
“…Both the ligands contain 5 histidines, but the alternate sequence seems to be more effective in binding the Cu(II) ion at physiological pH, in agreement with literature where it is reported that the alternate His-tag -AHAHAHAH-confers more stability to the Cu(II) complexes than the consecutive His-tag with four histidines. 27…”
Section: A Comparison About Metal Binding Abilitiesmentioning
confidence: 99%
“…This finding is also in good agreement with our previous findings that show that the more histidines are present in the peptide sequence, the more likely it is for amides to participate in Cu(II) binding at a higher pH than usual. 30 , 33 , 34 , 38 …”
Section: Resultsmentioning
confidence: 99%